A COMPARATIVE STUDY ON ADOLESCENT GIRLS’ GROWTH STATUS IN THE ENTREPRENEURIAL AND NON-ENTREPRENEURIAL FAMILIES- A CASE STUDY (International Journal of Food and Nutritional Sciences, 2022)
The study about the sustainable growth of adolescent girls in India. The mind of an entrepreneur is the most equipped to deal with the difficulties of tomorrow and navigate through the ever changing terrain of modern life. Entrepreneurs helped build this country and these same innovators continue to multiply its potential. Child in the economy can be a part of the new world of Entrepreneurship. To improve adolescent growth status government of India taking measures and providing services through Kishora Bala and Rajiv Gandhi Scheme for Empowerment of Adolescent Girls. Adolescence represents a window of opportunity to prepare for healthy adult life either it is personal or professional. The quality, productivity and high economic and social development in the economy always depends on growth status of adult’s life. Entrepreneurs helped build this country and these same innovators continue to multiply its potential. Child in the economy can be a part of the new world of Entrepreneurship. The basic qualities of confidence and competence, sound money management, leadership qualities, innovative ideas, and communicative skills in adolescents are the indications of entrepreneurial spirit. Nowadays, this adolescent’s entrepreneurial spirit captures global attention.